Metal-free oxidative cyclization of alkynyl aryl ethers to benzofuranones - Graf, Katharina; Rühl, Carmen L.; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2013)
Readily available phenols can be converted into substituted aryl alkynyl ethers, which react with an N-oxide as an oxidant and catalytic amounts of a Brønsted acid to provide benzofuranones. If non-terminal alkynyl ethers are applied, a 1,2-hydride shift takes place and phenyl acrylates are obtained. Thus activated alkynes can serve as α-oxy carbene precursors even in the absence of a metal catalyst.
Gesehen am 24.02.2020